Predicting sexual intention to engage in premarital sex among late adolescent in Kuantan government secondary schools: an application of the theory of planned behavior - Abdullah, Fa’iza; Draman, Samsul; Abd. Aziz, Karimah Hanim; Zainuddin, Nurul Akmanidar; Muhammad, Noor Azimah (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
The Theory of Planned Behavior (TPB) states that behaviour is determined by four main domains of social-cognitive factors; attitudes, social norms, self-efficacy and sexual intention. The aim of this study was to explore the correlation of the socio-cognitive factors predicting sexual intention to engage in premarital sex amongst late adolescent in Kuantan government secondary schools.